THE EFFECT OF E-DIGITAL NURSING CARE PLANS (E-DNCP) ON STUDENT SATISFACTION WITH PEDIATRIC NURSING DOCUMENTATION LEARNING MEDIA - Rini Wahyuni Mohamad; Cindy Puspita Sari Haji Jafar (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2025)
Introduction: Pediatric nursing is family-centered nursing care for children and efforts to prevent trauma to children in carrying out pediatric nursing care in the setting, students are guided by lecturers using documentation media. Technological advances are a challenge for lecturers to develop learning media that are not monotonous. Book-based learning media began to shift to digital-based learning media.Methods: This type of pre-experimental research with the research design used in this study is One Group Pre-Post Test Design. The sampling technique used cluster simple random sampling, for the intervention group as many as 48 students.Results: The average value of patient satisfaction level was obtained, namely pre-test 25.69 and post-test 36.08. Based on the Wilxocon test, the p-value is 0.000 (p-value 0.005), so it can be concluded that there is an effect of E-Digital Nursing Care Plan (E-DNCP) on the level of student satisfaction with pediatric nursing documentation learning media.Conclusion: There is an effect of e-digital nursing care plan (E-DNCP) on the level of student satisfaction with pediatric nursing documentation learning media.